Socioeconomic Impact of COVID-19 in MENA region and the Role of Islamic Finance - M. Kabir Hassan; Mustafa Raza Rabbani; Yomna Abdulla (Universitas Muhammadiyah Yogyakarta, 2021)
This paper analyses the socio-economic impact of the noble Corona virus (COVID-19) on ‘Middle East and North Africa’ (MENA) region as well as the role and opportunities of Islamic finance post COVID-19. The findings show that pandemic has affected the MENA region massively like any other region in the world. Since around 69% of the word’s crude oil supply is from this region alone, this causes it to suffer from dual shocks of COVID-19 pandemic as well as the declining crude prices that is caused by shocks from both ends, negative supply shock and a negative demand shock. The 19 countries in MENA region include from some of the richest countries of the world such as, Qatar, Kuwait, and Saudi Arabia, to some of the most vulnerable, poor and war ridden countries like Yemen, Syria, and Morocco. To mitigate the adverse effects of the pandemic, we suggest some immediate actions that can be taken such as a public fund to support health system, financial support to individuals and SME’s, financial support to corporations in order to prevent job loss and layoff and assurance of liquidity in domestic markets to prevent liquidity crunch. Finally, the paper analyses the role of Islamic finance in the region in recovery post COVID-19 and show that Islamic finance can be utilized as an alternative financial system in providing the relief to the COVID-19 affected people and entrepreneurs.